The Development of Blended Learning Courses Development of Education and Training Programs State University of Jakarta - Rita Mulyani; Dr. Robinson Situmorang, M.Pd; Imbar Kunto (Jurnal Pembelajaran Inovatif, 2021)
This research aims to develop a blended learning products to facilitate students in the course of the Development of Education and Training Programs in the environment of Educational Technology study programs, Jakarta State University. The research methods carried out are included in the Research and Development method. The research and development method adapted using the Dick and Carey system-based model and adding the ILDF (Integrated Learning Design Framework) model in step 7th of the Dick and Carey model. While the ILDF (Integrated Learning Design Framework) model is used as a product development model with steps, namely 1) Exploration, 2) Compilation, 3) Evaluation. Evaluations were carried out by expert reviews and one-to-one and small group user trials. The results of the three experts assessment showed 3,1 and the user trial showed 3,5. The development of blended learning courses The Development of the Training Program can be accessed on the moodle portal of Educational Technology and is expected to be able to facilitate the learning needs of students in the blended learning process especially in online learning (asynchronous).